Rozwój systemów franchisingowych w Polsce - Teneta-Skwiercz, Dorota (The Development of Franchising Systems in Poland, 2005)
In the first part of this article there are advantages and disadvantages of franchising presented. Moreover there is its essence described. Then the author tries to identify main barriers (obstacles) and agents which may contribute in the whole process of development of franchising systems. Finally, the meaning of franchising in polish economy has been shown and discerned.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 412-418